Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/1878-0261.12981
|View full text |Cite
|
Sign up to set email alerts
|

Novel CTRP8‐RXFP1‐JAK3‐STAT3 axis promotes Cdc42‐dependent actin remodeling for enhanced filopodia formation and motility in human glioblastoma cells

Abstract: C1q tumor necrosis factor-related peptide 8 (CTRP8) is the least studied member of the C1Q-TNF-related peptide family. We identified CTRP8 as a ligand of the G protein-coupled receptor relaxin family peptide receptor 1 (RXFP1) in glioblastoma multiforme (GBM). The CTRP8-RXFP1 ligand-receptor system protects human GBM cells against the DNA-alkylating damage-inducing temozolomide (TMZ), the drug of choice for the treatment of patients with GBM. The DNA protective role of CTRP8 was dependent on a functional RXFP1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 117 publications
2
7
0
Order By: Relevance
“…52 Several studies showed that the effect of CFL1 on the cellular activity is mediated by STAT3. 53,54 We confirmed that CFL1 expression was mediated by STAT3 (Supp.…”
Section: Discussionsupporting
confidence: 60%
“…52 Several studies showed that the effect of CFL1 on the cellular activity is mediated by STAT3. 53,54 We confirmed that CFL1 expression was mediated by STAT3 (Supp.…”
Section: Discussionsupporting
confidence: 60%
“…Using specific Rho kinase inhibitors targeting this pathway reduces the level of phosphorylated myosin II and cofilin, subsequently prevents tumor cell migration by inhibiting the dynamic assembly of f-actin structures. 101 P2Y2 nucleotide receptor (P2Y2R), 129 reticulon-4 isoform A (Nogo-A), 130 electroneutral Na + -K + -2Cl − -co-transporter1 (NKCC1), 131 miR-451, 132 C1q tumor necrosis factor-related peptide8 (CTRP8), 133 miR-29a/b/c 134 etc. are considered regulating phosphorylated LIMK1/2 and cofilin through targeting different members of Rho family of GTPases, including Rac1, the member A of Rho (RhoA) and CDC42, subsequently regulating glioma cell migration and invasion.…”
Section: Methodsmentioning
confidence: 99%
“…Binding of the leucine-rich G protein-coupled relaxin receptor RXFP1 to C1q-tumor necrosis factor-related protein 8 (CTRP8) ligand mediates increased GBM cell migration, protein kinase C pathway activation, and lysosomal protease cathepsin B production in glioblastoma progenitor cells ( 158 160 ). Additionally, RXFP1-CTRP8 promotes actin cytoskeletal remodeling and filopodia formation through STAT3 signaling, further enhancing glioblastoma migration ( 89 ). C1q/TNF-related protein 1 (CTRP1), a member of the CTRP family, is strongly correlated with glioblastoma multiforme (GBM) and can regulate CCL2 expression, promoting tumor progression ( 91 ).…”
Section: Relationship To Gliomamentioning
confidence: 99%